CTU Hornet 65 Niner: A network dataset of geographically distributed low-interaction honeypotsMendeley Data - Veronica Valeros; Sebastian Garcia (Data in Brief)
This data article introduces a new network dataset created to help understand how geographical location impacts the quality, type, and amount of incoming network attacks received by honeypots. The dataset consists of 12.4 million network flows collected from nine low-interaction honeypots in nine cities across the world for 65 days, from April 29th to July 1st, 2024. Each low-interaction honeypot was identically configured to capture incoming attacks using a state-of-the-art network flow collector, Zeek. Honeypots were distributed in nine cities: Amsterdam, Bangalore, Frankfurt, London, New York, San Francisco, Singapore, Toronto, and Sydney. The dataset is in JSON format and contains all types of Zeek network flow files, including protocol-specific logs.